PRADI cohort case‐control study on related factors of Alzheimer's disease: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Feliciano‐Astacio, Briseida E.; Beecham, Gary W; Silva, Concepcion; Mena, Pedro Ramon; Inciute, Jovita D.; Tejada, Sergio; Adams, Larry D.; Rodriguez, Vanessa C.; Celis, Katrina; Prough, Michael; Bussies, Parker; Sierra‐Lopez, Carolina B.; et al.
Abstract: Background: Alzheimer's disease (AD) has become a burden of social and economic importance, affecting millions of families and society at large. The Puerto Rico Alzheimer and Related Dementias Initiatives (PRADI) cohort was developed to investigate AD and genetics factors of AD in the Puerto Rican population. PRADI recruitment was a snowball sampling, with both island‐wide geographic distribution, as well as extensions to PR communities in the continental US. In this study we assessed the relationship between AD and cardiovascular risk factors of AD in the PR population. Method: We assessed over 700 elderly PR individuals for dementia, as well as medical history. Affection status was assessed using standard AD clinical criteria (NINCDS‐ADRDA) or mild cognitive impairment. All medical history was obtained by a self‐report or informant report. Differences between affected and unaffected were initially tested using a chi‐square test (for sex, diabetes, hypercholesterolemia, heart disease, hypertension, and stroke) and a t‐test for the age of the exam. Follow‐up analyses on stroke were performed using logistic regression with age at exam and sex as covariates in the model. Result: The analysis revealed no differences sex differences between AD and unaffected (p‐value > 0.05). Similarly, affected and unaffected showed similar levels of type 2 diabetes, hypercholesterolemia, heart disease, and hypertension (p‐value > 0.05). Affected individuals did however show an increase in stroke incidence (14.0% vs 5.2%; p‐value = 8.3e‐5). This difference persisted even when controlling for age of exam and sex. We did see a difference in age of exam between cases and controls, but this is likely due to ascertainment scheme. Conclusion: This analysis suggests that stroke may be a contributing factor to dementia in the PR population. However, given biases in the ascertainment scheme, additional assessments need to be performed. Additionally, work is ongoing to assess the role of ancestry and genetic factors in this association.